Desain Sistem Akuisisi Kecepatan Angin pada Menara SST Berbasis IoT - Rachman Rohendi; Herry Sujaini; Redi R. Yacoub; Bomo W. Sanjaya; Purwoharjono (Ikatan Ahli Informatika Indonesia (IAII), 2021)
Wind energy is one of the new renewable energy sources that can be used to generate electricity. The application of microgrids is expected to reduce the use of fossil fuels. PT PLN UP3B West Kalimantan has a greenfield type SST (Self Support Tower) communication tower with a height of 52 meters. This study aims to test the wind speed acquisition system in real-time on the SST tower. This research was conducted because there is no research on the design of the wind speed acquisition system on the SST Tower. Wind speed measurement data is obtained from the anemometer sensor mounted on the top of the SST Tower. The wind speed measurement data is sent to the MQTT broker and database using the MQTT protocol with the help of a microcontroller and communication media so that the measurement data can be monitored in real-time using the Grafana application either through local or public networks. The study was conducted from February 6 to 27, 2021. As a result, the wind speed data acquisition system managed to collect 5,501,689 wind speed measurement data stored in the database with an average wind speed of 3.03 m/s.